Armies and state-building in the modern Middle East : politics, nationalism and military reform - Cronin, Stephanie (London : I.B. Tauris, 2014)
Focusing on Iran, Afghanistan, and Saudi Arabia, adds an historical understanding to a contemporary political analysis of the roles of Middle Eastern armies, examining their structures, activities, and their role in state- and empire-building.
The military revolution in the Middle East -- Importing modernity : European military missions to Qajar Iran -- Building and rebuilding Afghanistan's army : an historical perspective -- The Iranian army under monarchy and republic : state-building, empire-building and revolution -- Tribes, coups and princes : building a modern army in Saudi Arabia.
Includes bibliographical references (pages 255-298) and index.
Keywords: Civil-military relations -- Middle East; Middle East -- Armed Forces -- Political activity; Middle East -- Armed Forces -- History -- 19th century; Middle East -- Armed Forces -- History -- 20th century; Middle East -- Armed Forces -- History -- 21st century